APLIKASI KONSEP REINVENTING GOVERNMENT, GOOD GOVERNANCE DAN NEW PUBLIC SERVICE DALAM PELAYANAN PUBLIK DI KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Yadi Lustiadi (Universitas Bandar Lampung (UBL), 2016)
Globalization no longer be at the weir, advances in information technology have supported change in the mindset of a nation to always follow the changes and demands of developing physical and social environment. The success and failure of a nation in the conduct of administrative reform, has more or less influence on other nations that do not want to miss implement the concept.Faced with the changes in society that is more intelligent and increasingly more demanding, the necessary role of government in providing services is tremendously effective, efficient and professional. Currently the government as public servants should strive for minimizing the gap between the demands of public service with the government's ability to comply, because of limited facilities and existing infrastructure can not be used as justification for the low quality of service to the community. Independence and reliable ability of the government is a basic requirement in order to keep the maintenance of public confidence in the government to meet all the needs of the service.To realize that goal, there should be the arrangement of government bureaucracy in order to build an effective government performance, efficient, and professional. At least, the stigma of the poor convoluted bureaucracy at both central government and regional levels can be reduced.From the results of the application of principle study that reinventing government applied but not yet fully fit is the principle of Competitive Government, this principle is in line with the principles of aid effectiveness and efficiency, Eccountability and Professionalism in GoodGovernance. Then the principle of reinventing government applied but erred in its application is the principle Enterpriting Government, is consistent with the principles of Professionalism, Effectiveness and efficiency as well as Eccountability in GoodGovernance. As well as the Application of reinventing government that can not be implemented is the principle of Market Oriented Government. This principle is actually aligned denganParticipation, Effectiveness and efficiency in Good Governance..